On the Role of Jacobian Terms in Maximum Likelihood Estimation - James G. MacKinnon (Queen's University, Department of Economics, 1978)
Because of the presence of Jacobian terms, determinants which arise as a result of a transformation of variables, many common likelihood functions have singularities. This fact has several implications for maximum likelihood estimation. The most interesting of these is that singularities often correspond with economically meaningful restrictions, and can be used to impose the latter. Several applications of this principle are presented. They suggest that maximum likelihood should be preferred to other estimation schemes not only because of its optimal large-sample statistical properties, but also because of its ability to incorporate certain a priori restrictions from economic theory.
Keywords: 330; Jacobian; maximum likelihood; loglikelihood; multiple maxima; singularity